Electricity Consumption and Economic Growth: A Linear and Nonlinear Causality Investigation for Turkey - PEMPETZOGLOU, Maria (International Journal of Energy Economics and Policy, 2014)
This paper aims to explore the potential linear and nonlinear causal relationship between electricity consumption and economic growth in Turkey during the time period 1945-2006. The study employs the standard linear Granger causality test and the nonparametric Diks and Panchenko causality test. Electricity consumption is disaggregated into residential and commercial electricity consumption, government offices, street illumination, industrial and other activities electricity consumption, in order to determine the sources of both linearity and nonlinearity. The findings provide evidence for the existence of a unidirectional nonlinear causality between income and electricity consumption at the aggregate level. The results also support the presence of a unidirectional linear flow running from economic growth towards residential, commercial and street illumination electricity consumption as well as a unidirectional nonlinear flow running from the residential and commercial electricity consumption towards economic growth and from income to electricity consumption for street illumination. Policies should focus on promoting electricity consumption, especially in the residential and commercial sectors to drive economic growth. Keywords: electricity consumption; economic growth; linear and nonlinear Granger causality JEL Classifications: Q43; Q48